2012
DOI: 10.1149/2.008210jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Additive Chemistry and Feature Size-Dependent Impurity Incorporation for Cu Interconnects

Abstract: The role of electrolyte additive chemistry in the incorporation of non-metallic impurities (such as C, S, and Cl) in electrodeposited Cu and its subsequent recrystallization behavior was characterized for both blanket electrodeposited Cu films and Cu plated into Damascene features. Chemistries yielding both pure and "doped" Cu were considered. For wide features (∼ >1 μm), impurity levels correspond well with blanket Cu film observations, while for narrow features (∼50 nm), impurity levels were elevated within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
3
9
0
Order By: Relevance
“…Organic additives are used in damascene Cu chemistries not only to achieve void-free metal filling process but also to control the impurity incorporation and grain structures of deposited Cu. The former is achieved as a result of the interplay between multiple additive components . The metal cation reduction kinetics are thus altered upon various mechanisms, such as an interaction between metal cations and additives in bulk electrolytes, the adsorption, desorption, and breakdown of a catalytic or inhibitive intermediate species adsorbed on the electrode surface, or competitive adsorption between multiple intermediates on the electrode surface. , These mechanisms at certain conditions can trigger electrochemical oscillation, where either the potential or current changes periodically within a certain range during galvanostatic or potentiostatic deposition, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Organic additives are used in damascene Cu chemistries not only to achieve void-free metal filling process but also to control the impurity incorporation and grain structures of deposited Cu. The former is achieved as a result of the interplay between multiple additive components . The metal cation reduction kinetics are thus altered upon various mechanisms, such as an interaction between metal cations and additives in bulk electrolytes, the adsorption, desorption, and breakdown of a catalytic or inhibitive intermediate species adsorbed on the electrode surface, or competitive adsorption between multiple intermediates on the electrode surface. , These mechanisms at certain conditions can trigger electrochemical oscillation, where either the potential or current changes periodically within a certain range during galvanostatic or potentiostatic deposition, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…They attributed this observation to the curvature enhanced accelerator coverage (CEAC) mechanism where the accelerator stayed on the Cu surface rather than getting incorporated. Kelly et al 11 recent published a study on the impurity in 50 nm wide lines, where an at least 10× increase was observed both in S and Cl. They also compared two different commercial plating chemistries known to incorporate different levels of impurities into blanket films and found no difference in the impurity in the narrow lines plated from these chemistries.…”
mentioning
confidence: 98%
“…10 In addition, an increased incorporation of nonmetallic impurities (C, O, S, Cl) in the Cu narrow lines during electroplating has been long observed. 9,11,12 A higher impurity level was known to hinder the Cu grain growth in blanket films [13][14][15][16] and thus could potentially account for the difficulty of grain grown in narrow lines as well.…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18][19] To achieve the goal of electronic circuit filling by copper deposits with excellent properties, organic additives are used, and these additives play critical roles in a copper plating bath. 8,10,[20][21][22][23] For microvia filling in PCBs, the specific copper electroplating formula must be capable of bottom-up filling or superfilling without formation of a void in the microvias. 12,[24][25][26] To satisfy this requirement, several organic additives, such as a suppressor, an accelerator, and a leveler, must be simultaneously added to the copper plating solution.…”
mentioning
confidence: 99%